Ratiometric Monitoring of Biogenic Amines by a Simple Ammonia-Response Aiegen - Xujing Guo; Xirui Chen; Rui Chen; Yujie Tu; Tianying Lu; Yuqian Guo; Liang Guo; Yonghua Xiong; Xiaolin Huang; Ben Zhong Tang (Foods, 2022)
Herein, we developed a paper-based smart sensing chip for the real-time, visual, and non-destructive monitoring of food freshness using a ratiometric aggregation-induced emission (AIE) luminogen (i.e., H+MQ, protonated 4-(triphenylamine)styryl)quinoxalin-2(1H)-one) as pH sensitive indicators. Upon exposure to amine vapors, the deprotonation of H+MQ occurs and triggers its color change from blue to yellow, with the fluorescence redshift from blue to amaranth. Consequently, we successfully achieved the sensitive detection of ammonia vapors by recording the bimodal color and fluorescence changes. Given the high sensitivity of H+MQ to ammonia vapor, a paper-based smart sensor chip was prepared by depositing H+MQ on the commercial qualitative filter paper through a physical deposition strategy. After being placed inside the sealed containers, the developed H+MQ-loaded paper chip was applied to the real-time monitoring of biogenic amine contents according to its color difference and ratio fluorescence change. The detection results were further compared with those obtained by the high-performance liquid chromatography method, which verified the feasibility of the designed paper chip for the food spoilage degree evaluation. Briefly, this work indicates that the designed H+MQ-loaded paper chip could be a promising approach for improving food freshness monitoring.